Growth of Weakfish Hatchery-produced Juveniles, Cynoscion Squamipinnis (Perciformes: Sciaenidae) in Captivity - Boza-Abarca, Jorge (2016)
Juveniles of weakfish, Cynoscion squamipinnis hatchery-produced from spontaneously spawning in captivity, were grown during 355 days at Estación de Biología Marina Juan Bertoglia Richards (Biology Marine Station John Bertoglia Richards) in Costa Rica. One hundred fifty two fish were stocked in tanks of four tonnes to a total biomass of 82 g m-3, and feeding with a diet of 50% protein, 17.5% carbohydrate, 11.8% lipids, 16% ash and 5% humidity. Dissolved oxygen was 7.12±1.13 mg L-1 (5.68 - 9.13 mg L- 1), salinity of 31.92±1.65 ups (29.84 - 34.71 ups), and temperature of 27.54±0.63°C (26.50 - 28.60°C), similar to the Gulf of Nicoya conditions. Initial mean weight was 3.77(1.15 g (0.3 - 6.2 g). Final mean body weight was 132.60(32.96 g (78.5 - 219.3 g). The growth (G) was 128.83 g, with a growth rate (GR) of 0.36 g d-1, and Specific Growth Rate (SGR) of 1.00 % BW d-1. The Relative Growth Rate (RGR) was 0.0053 g g-1 d-1. The feed conversion (FCA) during the period was 1.8±0.4. The weakfish had a lower growth parameters than other croaker species, the fish showed a calm behavior, accepted the pelletized diet, and they were easy to handle, characteristics which confirm that weakfish as potential candidate for commercial mariculture.